Teenagers' Media Consumption: Popular Sources and Their Trust Levels (Herald of Journalism, 2024)
More than 16 million representatives of the generation Z live in four Central Asian republics. This is a super-active media part of society, significantly ahead of other groups in media consumption. First, they are characterized by deep involvement in digital technologies. At the same time, young people are not only consumers of modern media but also information distributors: they write posts, post photos and videos, leave comments, and participate in solving social problems. The article examines the media consumption issues of Central Asia's generation Z, their attitude to the media, preferences and primary sources of information, and their level of trust in them. Media development in Kazakhstan, Uzbekistan, and Tajikistan is analyzed comparatively. The experience of the Kyrgyz Republic is also considered. The study aims to explore the transformation processes in the media space, identify current problems, and develop recommendations for improvement. The methodology uses sociological research, open data sources, and observations. The main results of the work are of practical importance for media and advertising specialists, marketers, and sociologists. Results also contains key points to consider in media education and information literacy.
Keywords: media, Central Asia, digital generation, media consumption, trust in media.